Teaching-learning through Edu Sat and 92 Academic Performance of Children : A Study - Dash, Manoj Kumar (INDIAN EDUCATIONAL REVIEW, 2009)
The programme of Sarva Shiksha Abhiyan (SSA) aims at providing access to quality education to all and improving professional competencies of various categories of teachers. Distance Education Programme (DEP) under SSA is a special component to supplement the traditional approach particularly for in-service teacher education programme. Implementation of EduSat through Rajiv Gandhi Project for EduSat Supported Elementary Education (RGPESEE) is a challenge in the light of potimum utilisation of communication technology for improving learning of children at elementary level. The first phase of this project focused on Sidhi district of Madhya Pradesh. The present paper addressed to reflect the effectiveness of implementation of EduSat on improving learning achievement of children in Mathematics at primary grade (standard III and V). At the same time attempt has been taken to campare learning achievement of children (belonging to ROT and non-ROT schoals) in Mathematics. The findings of the study aim at development of innovative strategies for effective implementation of EduSat in improving learning of children at elementary level and achieving the target of improving quality of elementary education all over the country.